Condition monitoring of VFT‐Rail® slab‐track railway bridges. Issue 3 (August 2016) - Pak, Daniel; Kopp, Maik; Feldmann, Markus; Seidl, Günter
Abstract: In 2010 the VFT‐Rail ® system was approved in accordance with CEN and railway standards by Germany's Federal Railway Authority (EBA) for operational testing. The approval was accompanied by a monitoring campaign on a VFT‐Rail ® bridge crossing the River Simmerbach. As a result of the positive experience gained during the operation of this bridge, two additional railway bridges were designed by SSF Ingenieure AG and put into service in 2014 by Deutsche Bahn (DB). To survey those bridges, a monitoring programme has been developed and instigated. The monitoring programme includes investigating the stress distribution between the concrete and specially designed composite dowels, which have a better fatigue resistance compared with conventional headed studs. The forces at several rail support points are also a focus of interest. The German railway operator DB Netz AG requested the survey to prove the applicability of state‐of‐the‐art calculation methods, which were not part of compulsory codes.